Peningkatan Citra dan Partisipasi Masyarakat melalui Optimalisasi Manajemen Humas di Yayasan Perintis Pendidik Nusa - Diantari, Shevia Dwi (Lembaga Yasin AlSys, 2025)
This research aims to improve the positive image of Yayasan Perintis Pendidik Nusa, strengthen community relations, and promote inclusive education programs. The main activities include managing social media to increase program visibility, creating PPDB brochures for promotion, and visiting parents' homes to strengthen relationships and encourage participation in supporting children's learning. This research uses descriptive qualitative method with data collection through observation, interviews, documentation, and direct involvement. Results show an increase in engagement on the foundation's social media, reflecting the success of the digital communication strategy. Home visits to students' parents also succeeded in building better collaboration, increasing parents' awareness of the importance of creating a supportive learning environment at home. Obstacles faced, such as limited human resources and time, are challenges that can be overcome through innovation in communication strategies and collaboration with student interns. This program is in line with SDGs number 4, which aims to ensure inclusive and equitable quality education. With high sustainability potential, this initiative can continue to contribute to improving the quality of education in the community and expand its positive impact in the future.